The effect of cyclic wetting and drying on the corrosion rate of steel in reinforced concrete - Golden, Gavin (Department of Civil Engineering, 2015)
Preventing chloride-induced reinforcement corrosion in marine concrete structures remains a concern for structural engineers. Marine structures are typically exposed to high chloride concentrations through direct exposure to sea water, which provides the primary conditions required for reinforcement corrosion. The progress of corrosion can be controlled through anodic, cathodic or resistivity processes. However, high chloride concentrations tend to prevent anodic control from governing the corrosion rate, while direct exposure to moisture generally prevents resistivity control. Consequently, cathodic control remains an important process in the marine environment to restrict the progress of corrosion. The primary cathodic reaction in reinforcement corrosion is the reduction of oxygen, and as a result the availability of oxygen is a key factor when considering reinforcement corrosion in the marine tidal zone. The corrosion rate may be effectively reduced if the drying time of the concrete during tidal cycles is sufficiently short, thereby reducing the oxygen supply at the level of the embedded steel.